Processes of resistance and collective reconstruction undertaken by women displaced by violence in Colombia (Polis (Santiago), 2018)
In the context of internal armed conflict in Colombia, the atrocity in violent acts is also transmitted to the family and community conflicts, and increases the politically forced displacement, which causes severe culture shock when weakening the patriarchal family structure, in gender roles and sexual practices. The article highlights the support provided by NGOs and international agencies to this phenomenon, presenting the cases of three groups of displaced women.
Keywords: Colombia; violence; women; forced political displacement